Phosphorus in batang ai hydroelectric dam Reservoir, Sarawak, Malaysia - Ling, Teck Yee; Lee, T.Z.E; Lee, Nyanti (International Digital Organization for Scientific Information, 2013)
Phosphorus is the nutrient that is responsible for eutrophication in reservoirs and lakes. Batang Ai Hydroelectric Dam Reservoir has been used for aquaculture for 20 years. However, little information is available on phosphorus concentration in the reservoir. Therefore, in this study, different forms of phosphorus were determined at six stations. Results shows that concentrations of total phosphorus depends on the season whereby rainy season and high water level showed lower concentrations (24.90-38.59 μg/L) than dry season and low water level (45.94-67.28 μg/L). In addition, during dry season, near the aquaculture station in the reservoir, higher total phosphorus (67.3 μg/L) but lower dissolved total phosphorus (23.90 μg/L) and higher organic fraction (25.55 μg/L) and lower dissolved organic fractions (9.74 μg/L) were observed. The second highest total phosphorus was located upstream in Batang Ai during wet season and it was high in organic form attributable to grey and black water and domestic animal waste. Outflow total phosphorus showed higher concentration during dry than wet season and it was much higher in dissolved organic form than dissolved reactive form. During dry season, outflow total organic phosphorus was twice the inflow but during wet season, the opposite was observed